Emergency intensive care unit pharmacist's intervention may reduce time to four-factor prothrombin complex concentrate administration: a retrospective study - Shoichi Imanaka; Tatsuro Kuwabara; Hiroto Ikeda; Yasufumi Miyake; Hiromi Enomoto; Tetsuya Sakamoto; Nobuhiro Yasuno (BMC, 2020)
Abstract Background Four-factor prothrombin complex concentrate (4F-PCC) must be administered as soon as possible, and in our emergency intensive care unit (EICU), pharmacists are available on weekdays for consultation on expediting 4F-PCC administration. Although recent reports have described a reduction in time to 4F-PCC administration, few studies have addressed if this is because of EICU pharmacist's intervention, and there are no such studies in Japan. Therefore, we aimed to examine whether EICU pharmacist's intervention reduced time to 4F-PCC administration. Methods This single-center retrospective cohort study was conducted from December 2017 to May 2019. We enrolled patients who received 4F-PCC due to major bleeding or requirement of urgent surgical/invasive procedures (n = 10). Patients were divided into two groups, namely, the intervention group (n = 5), in which EICU pharmacists consulted on weekdays, and the nonintervention group (n = 5), in which an intervention was not possible because of the absence of the EICU pharmacist. Results The median time from patient presentation to the EICU to 4F-PCC administration (103 min vs. 111 min, p = 0.4) was similar between the two groups; however, the median time from 4F-PCC prescription ordering to administration was significantly shorter in the intervention group than in the nonintervention group (21 min vs. 60 min, p = 0.02). Conclusions EICU pharmacist's intervention improves the process from 4F-PCC prescription to administration and can reduce time to 4F-PCC administration.